Microsatellites mining in Capsicum genomes and development of SSR markers in Capsicum baccatum - Das, Dilip Kumar; Ponnam, Naresh; Sandeep, V; Reddy, Anand C; Acharya, GC; Kumari, Meenu; Pradhan, SK (Vegetable Science, 2021)
Capsicum species is versatile vegetable cum spice crop,which have high commercial value because of its appealingcolor and pungency. Crop breeding and improvement ofchilli requires genomic resources. Computational mining ofchromosome wise microsatellites was carried out usingsearch criteria of minimum repeats of 12 for mono, 6 for diand 5 for tri, penta & hexa nucleotides and identified 130942,271650 and 2,78,143 perfect SSRs in C. baccatum cv. PBC81,C. annuum cv. Zunala and in C. chinense cv PI159236genomes, respectively. Of these perfect SSRs; 8999, 18060and 18019 were in compound form in the three speciesgenomes respectively. Overall density of SSRs/Mbpobserved was 173.66, 149.39 and 137.55 in C. baccatum, C.chinense and C. annuum. From 130942 perfect SSRs, total59510 primer pairs were designed in C. baccatum and 16SSR markers were primarily selected to test the usabilityand validated in a set of eight genotypes consisting of fouraccessions of C. annuum, one accession each of C. chinenseand C. frutescens and two accessions of C. baccatum. Allthe 16 SSR markers exhibited expected size of amplificationproduct. This C. baccatum based SSRs will be useful incharacterization of germplasm and marker assisted breeding